2022
DOI: 10.3389/fphar.2022.853971
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Profile of Endogenous Gamma-Hydroxybutyric Acid and its Biomarker Metabolites in Healthy Korean Females: Determination of Age-Dependent and Intra-Individual Variability and Identification of Metabolites Correlated With Gamma-Hydroxybutyric Acid

Abstract: Gamma-hydroxybutyric acid (GHB), used as a therapeutic and an illegal anesthetic, is a human neurotransmitter produced during gamma-aminobutyric acid (GABA) biosynthesis and metabolism. Potential biomarker metabolites of GHB intoxication have been identified previously; however, reference concentrations have not been set due to the lack of clinical study data. Urinary profiling of endogenous GHB and its biomarker metabolites in urine samples (n = 472) of 206 healthy females was performed based on differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
2
5
1
Order By: Relevance
“…Concentrations determined for organic acids 2,4‐DHB, 3,4‐DHB, GA, and succinylcarnitine in GHB‐negative cases were similar to ranges reported earlier in larger sample cohorts 28,33 . An exception was observed for SA in the present samples with determined concentrations exceeding those of former studies.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Concentrations determined for organic acids 2,4‐DHB, 3,4‐DHB, GA, and succinylcarnitine in GHB‐negative cases were similar to ranges reported earlier in larger sample cohorts 28,33 . An exception was observed for SA in the present samples with determined concentrations exceeding those of former studies.…”
Section: Resultssupporting
confidence: 88%
“…T A B L E 3 Unadjusted and creatinine-normalized concentrations of GHB, GHB conjugates, and organic acids determined in authentic samples Concentrations determined for organic acids 2,4-DHB, 3,4-DHB, GA, and succinylcarnitine in GHB-negative cases were similar to ranges reported earlier in larger sample cohorts. 28,33 An exception was observed for SA in the present samples with determined concentrations exceeding those of former studies. The observed instability of SA in the other studies 28,30,32 but not in the present study, might explain these discrepancies.…”
Section: Applicability and Limitationscontrasting
confidence: 93%
See 2 more Smart Citations
“…Moreover, it was previously reported that acute alcohol exposure alters the concentrations of dopamine, glutamic acid, and GABA in rats’ brains [ 62 , 63 ]. GHB is metabolized to 2,4- or 3,4-dihydroxybutyric acid or succinic acid which goes through the Krebs cycle [ 64 , 65 ] and then rapidly eliminated from the body in the form of carbon dioxide and water. GHB was detected only within 6 h in the blood and 12 h in urine after a single exposure to 60 or 50 mg/kg of GHB [ 16 , 66 , 67 ].…”
Section: Ghb Intoxication In Crimes Under the Influence Of Drugsmentioning
confidence: 99%